DAMPAK PENGGUNAAN GADGET TERHADAP PERILAKU REMAJA DALAM PERSPEKTIF RUANG LINGKUP SOSIOLOGI - Mayori, Yohana; Maunah, Binti (Cendekia: Jurnal Pendidikan dan Pembelajaran, 2022)
Abstract : The purpose of this research is to describe the behavior of adolescent gadget users by using theory from the scope of Gadget sociology, apart from being a tool to facilitate and assist humans in completing their work, it can also be the cause of behavioral deviations towards its users, especially among teenagers who are still mentally unstable and looking for his identity. There are so many adolescent behaviors that tend to experience significant changes after a long time and are accustomed to using gadgets. Childhood to adolescence is a period where Individuals carry out socialization to determine their role in community life. Socialization is a process of knowingly or unintentionally introducing the values ​​and norms of society in such a way that it forms a complete individual. To become a complete individual, each individual must take a role in a community group so that he is accepted as part of a community group. The method used is library research. The results of this study can be concluded (1) The scope of sociology (2) The need for socialization in order to form a complete individual (3) The behavior shown by some teenagers when using gadgets, namely, selfies, introverted, difficult to concentrate on the real world, social deviation, anti-social.